Genome-wide association study of vascular dementia - Schrijvers, Elisabeth; Hentschel, Frank (Stroke, 2012)
Background and Purpose—Most studies investigating the genetics of dementia have focused on Alzheimer disease, but little is known about the genetics of vascular dementia. The aim of our study was to identify new loci associated with vascular dementia. Methods—We performed a genome-wide association study in the Rotterdam Study, a large prospective population-based cohort study in the Netherlands. We sought to replicate genome-wide significant loci in 2 independent replication samples. Results—In the discovery analysis of 5700 dementia-free individuals, 67 patients developed incident vascular dementia over a mean follow-up time of 9.3±3.2 years. We showed genome-wide significance for rs12007229, which is located on the X chromosome near the androgen receptor gene (OR, 3.7; 95% CI, 2.3-5.8, per copy of the minor allele; P=1.3×10−8). This association was further confirmed in 2 independent populations (probability value of combined replication samples=0.024). Conclusions—Our study shows a novel genetic locus for vascular dementia on the X chromosome. Further replication of this finding is required.
Gesehen am 14.10.2020